Buckling and Postbuckling of Beams, Plates, and Shells - Eslami, M. Reza (Structural Integrity,, 2018)
This book contains eight chapters treating the stability of all major areas of the flexural theory. It covers the stability of structures under mechanical and thermal loads and all areas of structural, loading and material types. The structural element may be assumed to be made of a homogeneous/isotropic material, or of a functionally graded material. Structures may experience the bifurcation phenomenon, or they may follow the postbuckling path. This volume explains all these aspects in detail. The book is self-contained and the necessary mathematical concepts and numerical methods are presented in such a way that the reader may easily follow the topics based on these basic tools. It is intended for people working or interested in areas of structural stability under mechanical and/or thermal loads. Some basic knowledge in classical mechanics and theory of elasticity is required.